EFFECT OF INFORMATION PROCESSING AND DEPTH PERCEPTION UPON THROWING ACCURACY OF BASKETBALL PLAYERS - Virendra Kumar Singh; Chandrakant D. Agashe (Physical Education of Students)
Purpose: The purpose of the present study is to analyze throwing accuracy of basketball players in relation to their reasoning ability and depth perception. Materials and Methods : For present study, 200 intercollegiate basketball players (Ave. age = 21.34±1.87 years) were selected as sample. Johnson Basketball Throw for Accuracy (Passing Test) was the instrument which was used to assess shooting skills of selected subjects whereas reasoning ability of the selected subjects was assessed by MGTI prepared by Mehrotra (1984). To conduct the study, a 2x2 factorial design was used. Superior and inferior reasoning and perceptual abilities were ascertained by statistical method Q1 and Q3. 2x2 ANOVA results showed that the main effect of reasoning ability was not found to be statistically significant upon throwing accuracy of basketball players although it is close to .05 level of significance. Results : The main effect of depth perception upon throwing accuracy of basketball players turned out to be statistically significant. The two factor interaction effect of reasoning ability and depth perception upon throwing accuracy of basketball players was found to be statistically insignificant. Conclusion : It was concluded that reasoning ability and to some extent depth perception, are the two major variables which generate variance upon throwing accuracy of basketball players.